The application of near infrared spectroscopy (NIR) technique for - Sandor Barabassy (Mljekarstvo)
The production of cow’s milk in Hungary fluctuates by 15-20 % annualy. Surplus milk is dried into powder and can also be converted to modified milk powders using techniques such as ultra filtration. From approximetely 20.000 tonnes, of all milk powder types, 3.000 tonnes, is converted using ultra filtration technology. Multivariable near infrared (NIR) calibration was performed on powder mixtures of whole milk, skimmed milk, whey, retenate (protein concentrate) and lactose for rapid fat, protein, lactose, water and ash content determination. More than 150 samples were prepared and measured in two NIRS labs (Scottish Agriculture College – SAC – Aberdeen and University of Horticulture and Food Science - UHFS – Budapest). The results obtained from the same samples were compared. The aims of the study were: 1. Rapid quantitative and qualitative determination of mixtures of milk powder products using NIR technique. 2. Comparison of the results achieved in Aberdeen (SAC) and Budapest (UHFS) institutes. The mass per cent varied between 0.0-2.8% for fat, 0.0-80% for protein, 6.6-100 % for lactose, 0.0-5.0 % for water and 0.0-8.0 % for ash. High correlation coefficients (0.97-0.99) were found for all five components.